Silicon nanoparticles vs trace elements toxicity: Modus operandi and its omics bases - Mukarram, Mohammad; Ahmad, Bilal; Choudhary, Sadaf; Konôpková, Alena Sliacka; Kurjak, Daniel; Khan, M. Masroor A.; Lux, Alexander (Frontiers in Plant Science, 2024)
Phytotoxicity of trace elements (commonly misunderstood as 'heavy metals') includes impairment of functional groups of enzymes, photo-assembly, redox homeostasis, and nutrient status in higher plants. Silicon nanoparticles (SiNPs) can ameliorate trace element toxicity. We discuss SiNPs response against several essential (such as Cu, Ni, Mn, Mo, and Zn) and non-essential (including Cd, Pb, Hg, Al, Cr, Sb, Se, and As) trace elements. SiNPs hinder root uptake and transport of trace elements as the first line of defence. SiNPs charge plant antioxidant defence against trace elements-induced oxidative stress. The enrolment of SiNPs in gene expressions was also noticed on many occasions. These genes are associated with several anatomical and physiological phenomena, such as cell wall composition, photosynthesis, and metal uptake and transport. On this note, we dedicate the later sections of this review to support an enhanced understanding of SiNPs influence on the metabolomic, proteomic, and genomic profile of plants under trace elements toxicity.